Introduction to literary hermeneutics - Szondi, Peter 1929-1971 (Literature, culture, theory, 1995)
Peter Szondi is widely regarded as being among the most distinguished post-war literary critics. This first English edition of one of his most lucid and interesting series of lectures opens up his work in hermeneutics for English-speaking readers. The question of what is involved in understanding a text occupied Biblical and legal scholars long before it became a concern of literary critics. Peter Szondi here traces the development of hermeneutics through examination of the work of eighteenth-century German scholars. Ordinarily treated only as prefigurations of Schleiermacher, the work of Enlightenment theorists Johann Martin Chladenius, George Friedrich Meier, and Friedrich Ast yields valuable insight into the 'material theory' of interpretation, on which a practical interpretive methodology might be built